Democratic Republic of the Congo : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper takes stock of poverty in the Democratic Republic of the Congo (DRC). Poverty has receded in the DRC over the last decade on the back of gradual stabilization in the security and political situation, strong economic growth, and sharp decline in inflationary pressures. Most social indicators also improved during the period. However, poverty remains pervasive with a level still among the highest in sub-Saharan Africa, and DRC will likely not achieve any of the Millennium Developments Goals by 2015. Policy actions should focus on fostering the development of labor-intensive sector, increasing social spending, and redirecting public resources to the poorest regions of the country.